Informative and corrective responsive packaging: Advances in farm‐to‐fork monitoring and remediation of food quality and safety. Issue 5 (27th July 2021) - Zhang, Xinhui; Guo, Mingming; Ismail, Balarabe B.; He, Qiao; Jin, Tony Z.; Liu, Donghong
Abstract: Microbial growth and fluctuations in environmental conditions have been shown to cause microbial contamination and deterioration of food. Thus, it is paramount to develop reliable strategies to effectively prevent the sale and consumption of contaminated or spoiled food. Responsive packaging systems are designed to react to specific stimuli in the food or environment, such as microorganisms or temperature, then implement an informational or corrective response. Informative responsive packaging is aimed at continuously monitoring the changes in food or environmental conditions and conveys this information to the users in real time. Meanwhile, packaging systems with the capacity to control contamination or deterioration are also of great interest. Encouragingly, corrective responsive packaging attempting to mitigate the adverse effects of condition fluctuations on food has been investigated. This packaging exerts its effects through the triggered release of active agents by environmental stimuli. In this review, informative and corrective responsive packaging is conceptualized clearly and concisely. The mechanism and characteristics of each type of packaging are discussed in depth. This review also summarized the latest research progress of responsive packaging and objectively appraised their advantages. Evidently, the mechanism through which packaging systems respond to microbial contamination and associated environmental factors was also highlighted. Moreover, risk concerns, related legislation, and consumer perspective in the application of responsive packaging are discussed as well. Broadly, this comprehensive review covering the latest information on responsive packaging aims to provide a timely reference for scientific research and offer guidance for presenting their applications in food industry.